Estudo da atividade eletrocatalítica da reação de desprendimento de hidrogênio (RDH) sobre cátodos de níquel e níquel-molibdênio - Estumano, Gerson dos Santos (2009)
In this work it was accomplished studies about the hydrogen evolution reaction (HER) in alkaline middle under alloys of Ni-Mo obtained by electrodepositing in different operational conditions. By comparison, it was also made tests on the surfaces of Ni electrodeposited in the same conditions used for Ni-Mo alloy. For the alloy electrodepositing two electrolytic baths were prepared with Ni and Mo from different compositions and another bath just with Ni. The bath pHs were adjusted to the 9,5 value. The electrodeposits were obtained under galvanostatic control using plating solution with different molybdate ion concentration and current density of 50 mA cm-2. The substratum used was copper with 2 cm2 of geometric area. It was used three electric charge values: 50, 100 and 150C. Another study parameter was the employment of the ultra-sonic radiation in order to compare the electrodeposited alloys under the radiation effect with those obtained in absence. Two temperature conditions were used: room temperature (29°C) and 40°C. The amount of Ni and Mo on the electrodeposited surfaces was obtained by microanalysis of Energy Dispersive X-ray (EDX). The analysis of the superficial morphology of the layers was made using the Scanning Electron Microscopy (SEM). Electrochemical analyses were carried out by cyclic voltammetry in order to determinate the electrochemical active area on Ni and Ni-Mo surfaces. The better active areas samples were selected to others rehearsals. Tafel Diagrams were made, (maintaining stationary state, with the potenciostatic method, applying 20 different potentials inside of the strip of -1,6 V to - 0,95 V), in order to study the relation current-potential, the mechanism and the activation energy of RDH, in alkaline middle. The RDH mechanism used in the samples was the Tafel/Volmer type with the Volmer determining stage. A preferential nickel electrodepositing was observed, and by using ultrasound radiation waves it increased the amount of Mo and altered the morphology of the layers, producing, in some samples, cracks. The samples of Ni-Mo presented good stability in the long term test and minor activation energy values to the obtained for the Ni electrodepositing